Seeking care for epilepsy and its impacts on households in a rural district in southern Malawi - Alister Munthali; Stine H. Braathen; Lisbet Grut; Yusman Kamaleri; Benedicte Ingstad (African Journal of Disability, 2013)
Background: Epilepsy is a disability as defined in the 2012 Disability Act of the Government of Malawi. Objectives: This article explores the health-seeking behaviour of people with epilepsy in a rural town in southern Malawi and how having a person with epilepsy impacts on the households’ productivity.